(untitled) (Research, Society and Development, 2020)
This work had as main reason of its accomplishment to describe the main problems faced by the teachers, mainly those of public network and to show the importance of this theme since it interferes in the quality of the teaching of the students and to deepen a work already accomplished. Therefore, the school reality in physics education faces serious problems such as students’ lack of interest, demotivation and teacher malaise in the area, in which it is greatly affected by the bad working conditions, poorly paid professionals and the poor infrastructure of the institutions, a mechanical form of teaching driven by the lack of equipment and laboratories. The main objective throughout this work is to point out the main difficulties faced in the teaching of physics, which leads to teacher malaise that consequently interferes in education, causing the removal of professionals or interfering in the quality of teaching. And from a bibliographic research, develop or encourage the creation of new perspectives for teaching, contributing both to the development of the student and the teacher. However, teaching can contribute significantly, through more efficient ways to teach the discipline for better working conditions, for this it is necessary to implement and use appropriate laboratories and equipment, so that the professional does not work only in the classroom classroom with theories and memorization of formulas, but also in extra-class times, such as scientific research and carrying out experiments.